1995
DOI: 10.1017/s0317167100040452
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Baclofen Therapy for Adults with Spinal Spasticity: Therapeutic Efficacy and Effect on Hospital Admissions

Abstract: ABSTRACT:A prospective trial to demonstrate the efficacy of intrathecal baclofen therapy by implanted pump for adults with spasticity due to spinal cord injury or multiple sclerosis was initiated in our hospital. Of the 140 patients assessed, 7 met the following criteria for inclusion in the study: a modified Ashworth score > 3, a spasm frequency score > 2, and an inadequate response to oral antispasticity drugs, (i.e., baclofen, clonidine and cyproheptadine). All patients responded to intrathecal bolus inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…(5) Intrathecal baclofen (ITB) therapy has now become a widely recognised treatment for severe, disabling spasticity in individuals with cerebral palsy, stroke, and spinal cord and brain injuries. (6)(7)(8)(9)(10)(11)(12)(13)(14) Other benefi ts of ITB therapy include reduction of central pain, improvement in cerebral dysautonomia and improvements in disorders of consciousness. (15,16) Despite the established therapeutic value of ITB therapy, there is a paucity of local literature.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Intrathecal baclofen (ITB) therapy has now become a widely recognised treatment for severe, disabling spasticity in individuals with cerebral palsy, stroke, and spinal cord and brain injuries. (6)(7)(8)(9)(10)(11)(12)(13)(14) Other benefi ts of ITB therapy include reduction of central pain, improvement in cerebral dysautonomia and improvements in disorders of consciousness. (15,16) Despite the established therapeutic value of ITB therapy, there is a paucity of local literature.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed no significant difference between patients and controls in the number of hospital days in the year following CIBI. For the implantation year there were 18.7 days used on average by the control group compared with an estimated average of 20.7 days related to the CIBI procedure and no further days related to spasticity for the CIBI group.These papers provide three separate estimates of bed days used for patients without or prior to CIBI: 19 days, 89 32 days (63 days over 2 years) 88 and 84 days. 68 The differences are almost certainly due to differences in patient selection and care settings.…”
mentioning
confidence: 99%
“…1,2,4,7,12,[17][18][19][20][21] Cost per QALY ranged from $10,550 to $19,570, well below the $50,000 willingness-to-pay for 1 QALY regarded as the guideline for evaluating the value of medical technologies. In the present study, the cost per QALY of ITB therapy in Japan was 1,554,428 yen, or $19,430 in U.S. dollars, far below the $50,000 figure.…”
Section: Mobilitymentioning
confidence: 99%